Peningkatan Pemahaman Digital Footprint Dengan Edukasi Dasar Komunikasi Di Sosial Media Kepada Pemuda Desa Adat Tulikup, Gianyar, Bali - anak agung ngurah bagus aristayudha aristayudha (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Indonesia has experienced a significant increase in internet usage on an annual basis. The massive use of social media and the internet will further accelerate the spread of bad information and content if it is not prevented by being a wise citizen in the digital world. The purpose of holding this education is to increase public literacy in the safe use of digital media and improve good ways of communicating in digital spaces and promote indonesian culture properly so as to support the smart village movement. This activity starts from the planning stage which produces a Term of Reference (TOR) which then explains the time and place of implementation of the activity, resource persons and participants of the activity. It is hoped that further community service activities can organize more of these activities and also reach a wider community.